Evaluation of mixed microalgae species biorefinery of Desmodesmus sp. And Scenedesmus sp. For bioproducts synthesis - Tang, Doris Ying Ying (2023)
Microalgae is known to produce numerous bioactive compounds for instance proteins, fatty acid, polysaccharides, enzymes, sterols, and antioxidants. Due to their valuable biochemical composition, microalgae are regarded as a very intriguing source to produce novel food products and can be utilised to improve the nutritional content of traditional foods. Additionally, microalgae are used as animal feed and additives in the cosmetics, pharmaceutical as well as nutraceutical industries. As compared to other terrestrial plants and other microorganisms, microalgae possess few advantages: (1) rapid growth rate; (2) able to grow in non-arable land and harsh cultivation conditions; (3) low nutritional requirements; (4) high productivity; and (5) reduce emission of carbon dioxide. Despite the large number of microalgae species found in nature, only a few species are identified and commercialized such as Chlorella sp., Spirulina sp. Haematococcus pluvialis, Nannochloropsis sp. and Chlamydomonas reinhardtii, which is one of the major obstacles preventing the full utilisation of microalgae-based technology.